Batch-mode microfluidic radiosynthesis of N-succinimidyl-4-[F-18]fluorobenzoate for protein labelling - Bejot, R; Elizarov, A; Ball, E; Zhang, J; Miraghaie, R; Kolb, H; Gouverneur, V (2011)
The batch microfluidic technology is a promising system for sequential chemical steps combining the advantages of micro-scale reactions, while addressing some shortcomings of flow-through systems. We report herein the convenient three-step, one-pot synthesis and purification of [ 18F]SFB. [ 18F]SFB is a radiolabelling agent that can be used to label sensitive biomolecules, which are not accessible by direct nucleophilic 18F-fluorination. Five sequential steps were performed with a batch microfluidic device to obtain the short-lived positron-emitter- labelled molecule. Aqueous [ 18F]fluoride was concentrated and further eluted to a microreactor for evaporation. Nucleophilic 18F- fluorination of the precursor was carried out at high temperature, prior to hydrolysis and subsequent activation of the 4-[ 18F]fluorobenzoyl group. Purification on miniaturized solid-phase finally afforded [ 18F]SFB in 25 min and 55±6% yield (not decay-corrected) and >98% radiochemical purity. In this study, microfluidic prepared [ 18F]SFB could be further successfully used for labelling the epidermal growth factor protein. These results illustrate how microfluidic batch devices are advantageous for producing radiotracers for molecular imaging, e.g. Positron emission tomography. The technology offers many benefits such as the possibility to use much smaller quantities of starting material, reduced reaction time combined with improved efficiency, and easier purification. Copyright © 2010 John Wiley and Sons, Ltd.